FESYEN ANIME JEPANG SEBAGAI KAJIAN BUDAYA POPULER - Adhitiya Prasta Pratama (JURNAL SOSIAL Jurnal Penelitian Ilmu-Ilmu Sosial, 2021)
At this time, the media act as the mastermind behind the formation of popular culture. Media shapes the reality of human life. Thus, humans are trapped in false needs. Today's popular culture comes through a new form, namely the Japanese anime fashion. Japanese anime fashion has emerged as a representation of popular culture in the Asian sphere. Apart from that, Japanese anime fashion also plays a role in the culture industry. This writing uses the literature method to obtain data. Furthermore, this paper also uses a theory based on the theory of Popular Culture by Dominic Strinati. Thus, this writing seeks to reveal, unravel, and explain that Japanese anime fashion is present as a popular culture that cannot be realized. Therefore, with the presence of popular culture, people, especially teenagers, seem to be immersed in surface, trivial, pragmatic, and commercial realities.